Оцінка гідрохімічного режиму та якість поверхневих вод басейну р. Інгулець - Кравчинський, Р.Л. (Інститут геологічних наук НАН України, 2009)
Проанализированы сезонная динамика основных составляющих химического состава вод рек Ингулец и Саксагань, а также показано экологическое состояние всей гидроэкосистемы. На основе детального анализа литературных источников установлены основные факторы, которые влияют на качество водных ресурсов исследуемого региона. In this article it is analysed the seasonal dynamics of basic constituents the chemical composition of waters of the rivers Ingulets and Saksagan and also shown the ecological state of gydroekosistem. On the basis of the detailed analysis the rows of literary sources are shown basic factors which influence on quality the surface water of the probed region.